MENINGKATKAN KUALITAS PENULISAN KARYA ILMIAH GURU-GURU SEKOLAH MENENGAH ATAS DI PARAKAN TEMANGGUNG - Rochmad, Rochmad; Agoestanto, Arief; Kharis, Muhammad (Rekayasa : Jurnal Penerapan Teknologi dan Pembelajaran, 2016)
Partners of this community service wereMadrasah Aliyah Negeri Parakan and SMK 17 Parakan Temanggung, Temanggung. This community serviceactivity was aimed atovercoming some of the problems faced by the teachers in both partners related to improving the quality of teaching in the class and writing scientific papers. The problems were low quantity and quality of the scientific work of the teachers. This community service included: the workshopof developinginnovative and creative learning media based on curriculum 2013; workshopaction research proposal writing; facilitationduring the implementation and writingthe report of action research; mentoring during the writing of scientific articles based on the results of the action research; and facilitation of scientific articles publication in scientific journals. The product expected in this community service was a collection of learning methods using the scientific approach based on the curriculum of 2013.